2017
DOI: 10.1002/hep.29359
|View full text |Cite
|
Sign up to set email alerts
|

The presence and severity of nonalcoholic steatohepatitis is associated with specific changes in circulating bile acids

Abstract: NAFLD is associated with significantly altered circulating BA composition, likely unaffected by type 2 diabetes, and correlated with histological features of NASH; these observations provide the foundation for future hypothesis-driven studies of specific effects of BAs on specific aspects of NASH. (Hepatology 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
329
2
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(370 citation statements)
references
References 39 publications
26
329
2
13
Order By: Relevance
“…Regarding circulating BAs, the main difference between the two phenotypes was the reduction of the primary BAs and the increase of the secondary BAs in the protected group. This is in agreement with a recent study which described increased primary and reduced secondary BAs in serum of NAFLD and NASH patients . Previous studies have also reported an increase in serum and fecal primary BAs in NAFLD patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding circulating BAs, the main difference between the two phenotypes was the reduction of the primary BAs and the increase of the secondary BAs in the protected group. This is in agreement with a recent study which described increased primary and reduced secondary BAs in serum of NAFLD and NASH patients . Previous studies have also reported an increase in serum and fecal primary BAs in NAFLD patients.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, supplementation of a HFD with soybean protein increased the secondary/primary BA ratio in mice, conferring metabolic benefits . This increase in primary BAs in NAFLD could be attributed to an enhanced synthesis through CYP7A1, the rate‐limiting enzyme in this process, that has been reported to be overexpressed in NAFLD patients and HFD‐fed rats . In the present study, CYP7A1 downregulation has been shown in protected mice, justifying the reduction in primary αMCA and βMCA.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, plasma level of glycocholate, taurocholate, glycochenodeoxycholate, taurochenodeoxycholate and ursodeoxycholic acid were increased in patients with NASH compared with patients with NAFL 87. Levels of taurolithocholic acid, glycocholate and taurocholate correlated with severity of portal inflammation, lobular inflammation, steatosis and hepatocyte ballooning, respectively 87. The ratio of DCA to CDCA was significantly increased in patients with NASH,70 84 85 and levels of FXR were lower in liver tissues from paediatric patients with NAFLD compared with healthy children 88.…”
Section: Microbiota-derived Metabolites In Nafldmentioning
confidence: 92%
“…Interestingly, another research group found that liver levels of cholic acid and DCA were significantly decreased in patients with NASH 86. In addition, plasma level of glycocholate, taurocholate, glycochenodeoxycholate, taurochenodeoxycholate and ursodeoxycholic acid were increased in patients with NASH compared with patients with NAFL 87. Levels of taurolithocholic acid, glycocholate and taurocholate correlated with severity of portal inflammation, lobular inflammation, steatosis and hepatocyte ballooning, respectively 87.…”
Section: Microbiota-derived Metabolites In Nafldmentioning
confidence: 99%
“…In line with this hypothesis, the investigators show that the expression of SHP (positive FXR target) is markedly down‐regulated in livers of patients with NAFL or NASH, whereas cholesterol 7 alpha‐hydroxylase (CYP7A1; negatively regulated by FXR through small heterodimer partner [SHP]) is strongly induced. Consistently, serum 7‐alpha‐hydroxy‐4‐cholesten‐3‐one levels are increased in NASH . Whether CDCA‐mediated induction of FXR transcriptional activity is, in fact, modulated by CA has, however, not been formally tested on the molecular level.…”
mentioning
confidence: 99%